MESIN PEMERAS KELAPA PARUT MENJADI SANTAN SISTEM ULIR TEKAN PENGGERAK MOTOR LISTRIK 1 HP - Abdul Syukur Alfauzi; Rofarsyam Rofarsyam (Teknoin, 2005)
The squeezing process of grated coconut into coconut milk, and the following process of  making the milk into coconut oil, which is done by people living in rural areas, is until now still very traditional. They do it manually (by hands) so that they produce 7.2 kg/hour grated coconut or 3.6 litres/hour thick coconut milk.To effectify the process, the squeezing needs to be mechanized, using a grated coconut squeezer machine.The machine is designed on the basis of Screw Press system with a ¼ HP 1450 rpm electric motor power using a pulley belt transmission and a gear box. The squeezer’s force refers to coconuts aging between 341 and 413 days (hand squeezing force normally practised by coconut oil producers in rural areas).This prototype of machine has the capacity of producing 53.2 kg/hour grated coconut or 26.6 litres/hour thick coconut milk, which has similar quality (in colour, smell and texture) as that manually squeezed.Keywords : grated coconut squeezer, coconut milk